One-way spillovers, endogenous innovator/imitator roles and research joint ventures - Rabah Amir; John Wooders (Institute for Advanced Studies (IHS), 1997)
We consider a two-period duopoly characterized by a one-way spillover structure in process R&D and a very broad specification of product market competition. We show that a priori identical firms always engage in different levels of R&D, at equilibrium, thus giving rise to an innovator/imitator configuration and ending up with different sizes. In view of this endogenous firm heterogeneity, the social benefits of, and the firms' incentives for, research joint ventures are somewhat different from the case of ex post firm symmetry. The key properties of the game are submodularity (R&D decisions are strategic substitutes) and lack of global concavity.
Keywords: C72; L13; O32; 330; oligopolistic R&D; one-way spillovers; research joint ventures; submodularity